Modal properties and seismic behaviour of buildings equipped with external dissipative pinned rocking braced frames. (1st October 2018) - Gioiella, L.; Tubaldi, E.; Gara, F.; Dezi, L.; Dall'Asta, A.
Highlights: Innovative external seismic protection system based on a pinned rocking tower. The system provides a regularization of interstorey drifts and added damping. State-space reduced formulation for dynamic behavior and seismic analysis. A case study (Van Nuys building) before and after the retrofit is analyzed. Contribution of high order modes to dynamic response parameters. Abstract: This paper deals with the seismic protection of building frames by means of external dissipative systems. Dampers and external framing system can be arranged in several configurations, involving different kinematic behaviours and seismic performances. This study analyses a recently-developed solution called "dissipative tower", which exploits the rocking motion of a steel braced frame, hinged at the foundation level, for activating the dampers. This system aims at controlling both the global response and the local storey deformation of the frame, by using a reduced number of viscous dampers. A state space formulation of the dynamic problem is presented in general terms, together with the solution of the seismic problem via the modal decomposition method. A parametric study is carried out to evaluate the influence of the added damping and of the braced frame stiffness on the modal properties and seismic response of a benchmark reinforced concrete frame retrofitted with the external dissipative towers. It is shown that the addition of the towers yields a regularization and reduction of the drift demand along the building height, but it may induce significant changes, not always beneficial, in the distribution of internal actions of the frame and in the absolute storey accelerations.